Family Empowerment as Nursing Intervention for Families with Type 2 Diabetes Mellitus: A Literature Review - Setyoadi; Seda, Lukas Fransiskus Saverius; Lestari, Puji; Irwando, Erdy; Nurani, Nunik; Hayati, Yati Sri; Kristianingrum, Niko Dima; Kartika, Annisa Wuri (Al-Hijrah Indonesia, 2023)
Background: This literature review is motivated by the empirical phenomenon that illustrates the increasing number of Type 2 Diabetes mellitus (T2DM) patients, which has an impact on family caregivers. The chronic condition of T2DM requires long-term care and monitoring to maintain blood glucose levels within normal limits. Family caregivers play a crucial role in assisting family members with T2DM by enhancing their roles and functions through family empowerment. Purpose: This literature review aimed to theoretically analyze the importance of family empowerment as a nursing intervention in improving the health status of family members with T2DM. Methods: The research method used in this study is a literature review, which includes an analysis of 9 articles obtained from three databases: ProQuest, Science Direct, and Google Scholar. The search keywords used for article retrieval included